Actualized inventory of medicinal plants used in traditional medicine in Oaxaca, Mexico - Cruz-Pérez Alejandra Lucía; Barrera-Ramos Jacqueline; Bernal-Ramírez Luis Alberto; Bravo-Avilez David; Rendón-Aguilar Beatriz (BMC, 2021)
Abstract Background Oaxaca is one of the most diverse states in Mexico from biological and cultural points of view. Different ethnic groups living there maintain deep and ancestral traditional knowledge of medicinal plants as well as traditional practices and beliefs about diseases/illnesses and cures. Previous ethnobotanical research in this state has helped document this knowledge, but with the addition of more studies, more records appear. We updated the inventory of medicinal knowledge between the different ethnic groups that inhabit the Oaxacan territory. Methods A database was constructed from two sources: (1) original data from a 3-year project in 84 municipalities of Oaxaca inhabited by eight ethnic groups and (2) different electronic databases. Results Records of 1032 medicinal plants were obtained; 164 families were registered, with Asteraceae, Fabaceae, and Rubiaceae being the most commonly used. A total of 770 species were reported in 14 vegetation types; the most important species came from temperate forests. Only 144 species corresponded to introduced species, and 272 were listed in a risk category. Illnesses of the digestive and genitourinary systems as well as culture-bound syndromes were treated with high numbers of medicinal plants. The Mestizo, Mixe, Mixtec, and Zapotec ethnic groups exhibited the greatest number of recorded medicinal plants. The 17 species that were used among almost all ethnic groups in Oaxaca were also used to cure the highest number of diseases. Discussion Inventories of medicinal plants confirm the persistence of traditional knowledge and reflect the need to recognize and respect this cosmovision. Many species are gathered in wild environments. The most important illnesses or diseases recorded in the present inventory are also mentioned in different studies, suggesting that they are common health problems in the rural communities of Mexico. Conclusions Medicinal plants are essential for ethnic groups in Oaxaca. It is necessary to recognize and understand the complex ancestral processes involved in the human-nature interaction and the role of these processes in the conservation of biodiversity and in the survivorship of ethnic groups that have persisted for centuries. Finally, this study serves as a wake-up call to respect those worldviews.